Occupational Therapy in Stroke: A Case Study Using the Bobath Frame of Reference and Task Oriented Approach - Nur Arsyi, Reza; Afifah Fadhilah Nursyam; Muhammad Luthfi; Hermito Gidion; Ayleen Alicia Kosasi; Erna Faryza Mohd Poot; Rosilah Wahab; Nur Atiqah Azman (Jurnal Fisioterapi Terapan Indonesia, 2024)
Stroke is a sudden neurological disorder caused by vascular injury to the brain, leading to significant functional limitations. This case study examines the use of occupational therapy interventions, specifically the Bobath and Task Oriented approaches, for a 43-year-old male with left hemiparesis to enhance independence in motorcycling. The patient experienced various limitations, including vestibular function, range of motion, muscle tone and strength, postural control, and fine motor skills. Using the Ashworth scale and the Canadian Occupational Performance Measure (COPM) for assessment, occupational therapy interventions showed progress in several aspects, although the primary goal has not yet been fully achieved. This study highlights the importance of intensive and ongoing occupational therapy to improve patient independence in daily activities.